Underwater hybrid energy harvesting based on TENG-MTEG for self-powered marine mammal condition monitoring system. (March 2023) - Liu, C.; Qu, G.; Shan, B.; Aranda, R.; Chen, N.; Li, H.; Zhou, Z.; Yu, T.; Wang, C.; Mi, J.; Xu, M.
Abstract: To effectively protect endangered marine mammals, one needs to collect and monitor their biological data and living environment information. This is however a great challenge for the endurance of marine mammal condition monitoring devices. The present study is to propose a self-powered marine mammal condition monitoring system, based on the hybrid energy harvesting mode of triboelectric nanogenerator (TENG) and micro thermoelectric generator (MTEG), to address the challenge. This system not only can obtain energy from the movement of marine mammals but also harvest energy from the temperature difference between the body surface and the ambient. The system fittingly integrates oscillating-TENG (O-TENG), MTEG, and power management unit. Note that O-TENG and MTEG can produce the maximal open circuit voltages of 5.85 V and 1.821 V, respectively. The TENG + MTEG hybrid energy harvesting device can improve the energy collection and battery charging performance by 4.93% compared with the MTEG single energy acquisition device. Hence, it can prolong the service life of the device, achieve an excellent stability, and is easy to manufacture. Eventually, the system can provide an effective and long-term endurance strategy for the condition monitoring device of endangered marine mammals. Graphical abstract: Image 1 Highlights: New hybrid energy harvesting mode based on MTEG and TENG. It is the first time to employ marine mammals as the hybrid energy harvesting carrier to realize the self-energy supply of marine mammals' condition monitoring system. The hybrid energy harvesting device can charge a lithium polymer battery by using the power management control unit. Compared with employing the MTEG device as the only energy source, the present MTEG + TENG system can improve the energy collection and charging performance by 4.93%.